MODEL PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL SECARA NON LITIGASI BERBASIS NILAI KEADILAN SOSIAL - Mashari Mashari (Faculty of Law, Universitas Diponegoro, 2012)
Abstract The aim of Act No. 2 Year 2004 about conflict settlement of industrial settlement normatively is very noble to realize harmonious, dynamic, and fair industrial relation for optimal based on the values of Pancasila, also the need of arranging institution and mechanism of conflict settlement of industrial relation in fair non-litigation way. The model of conflict settlement of industrial relation in ideal non-litigation way through involvement from government as regulator in the field of employment for balancing the bargaining position between employee and employer in order to create non-litigation conflict setlement of industrial relation with social justice valuea as the base. Keywords: Conflict settlement of industrial relation in non-litigation way, Social Justice Abstrak Cita-cita Undang-Undang No. 2 Tahun 2004 tentang Penyelesaian Perselisihan Hubungan Industrial secara normatif amatlah luhur untuk mewujudkan hubungan industrial yang harmonis, dinamis, dan berkeadilan secara optimal berdasarkan nilai-nilai Pancasila, serta perlunya penyediaan institusi dan mekanisme penyelesaian perselisihan hubungan industrial secara non litigasi yang berkeadilan. Model penyelesaian perselisihan hubungan industrial secara non litigasi yang ideal melalui campur tangan pemerintah sebagai regulator di bidang ketenagakerjaan untuk keseimbangan posisi tawar antara pekerja dan pengusaha, sehingga terciptanya penyelesaian perselisihan hubungan industrial secara non litigasi yang berbasis nilai keadilan sosial. Kata kunci: Penyelesaian perselisihan hubungan industrial secara non litigasi, Keadilan sosial